Inovasi Peningkatan Hasil Tangkapan Ikan Produk Unggulan Daerah oleh Nelayan Purse Seine Menggunakan Teknologi GPS - Zaenal Arifin; Buang Budi Wahono; Dias Prihatmoko; Sisno Riyoko (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2020)
Livelihoods as fishermen are the backbone for people who live near the coast, it is not much different from the people in Jobokuto village, Jepara Regency who also work as fishermen, so far the catches of fishermen after getting catches of fish are directly sold to middlemen or local fish auction sites, so that fishermen cannot increase fish catches to be processed into commodities that have high economic value so that their economy can increase. Based on this description, service activities are carried out to fishermen by providing training ranging from the potential of fisheries, the superiority of GPS and Sounder technology, increased catches on processed fish and stabilization of processed fish equipment ranging from fish shredder, shredded cooker, shredded slicer, bender, spinner as well as tools fish smoke. Some of these activities are expected to result in the end that fishermen SMEs can develop their businesses, increase catches and sales, and improve the welfare of fishermen in Jepara Regency. The activity is also expected to be a pilot project for other fishermen in the district in implementing fishing technology using a fish finder with the use of appropriate technology that is environmentally friendly.